2015
DOI: 10.1111/are.12858
|View full text |Cite
|
Sign up to set email alerts
|

Dietary vitamin C requirement of juvenile Chinese sucker (Myxocyprinus asiaticus)

Abstract: An 8-week growth experiment was conducted to quantify the appropriate dietary vitamin C requirement of juvenile Chinese sucker (Myxocyprinus asiaticus). Triplicate groups of 30 experimental fish [initial body weight: (7.1 AE 0.3) g] were cultured in 500 L aquaria and fed with semi-purified diets containing six levels [10.1 (unsupplemented diet), 37.4, 64.9, 125.2, 244.2 and 482.0 mg kg À1 diet, respectively] of vitamin C (supplied as L-ascorbyl-2-polyphosphate). Results showed that weight gain of Chinese sucke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 37 publications
13
27
1
Order By: Relevance
“…Alkaline phosphatase (ALP) is a key hydrolase enzyme in hydrolysing the phosphate groups from many molecules, such as nucleotides, proteins and alkaloids. Earlier studies had also proved that ALP can helps in utilization of L‐ascorbyl‐2‐polyphosphate and a raise in ALP was found in intestine when the fish fed with Vitamin C supplemented diet using L‐ascorbyl‐2‐polyphosphate (Huang et al., ). Fish fed a diet with 35 mg AA/kg and 70 mg AA/kg levels had higher ALP activity than did other treatments.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Alkaline phosphatase (ALP) is a key hydrolase enzyme in hydrolysing the phosphate groups from many molecules, such as nucleotides, proteins and alkaloids. Earlier studies had also proved that ALP can helps in utilization of L‐ascorbyl‐2‐polyphosphate and a raise in ALP was found in intestine when the fish fed with Vitamin C supplemented diet using L‐ascorbyl‐2‐polyphosphate (Huang et al., ). Fish fed a diet with 35 mg AA/kg and 70 mg AA/kg levels had higher ALP activity than did other treatments.…”
Section: Discussionmentioning
confidence: 95%
“…The optimization of vitamin C needs careful examination of liver because the suboptimal level of vitamin C in diet could damage the proper functioning of liver (Huang et al, 2015). The AST and ALT are the transaminase enzymes that play a key role in the catalytic process and reciprocal transformation of amino acids, lipids and carbohydrates (Lin & Luo, 2011;Ramaswamy, Thangavel, & Selvam, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these radicals are reactive oxygen species (ROS), such as the hydroxyl radical, hydrogen peroxide and superoxide anion, all of which have the propensity to damage crucial cellular components like lipids, carbohydrates, proteins and DNA (Finkel & Holbrook ; Huang et al . ).…”
Section: Vitamins C (Aa) and E (α‐Tocopherol α‐Toc) As Antioxidant Amentioning
confidence: 97%
“…) and reducing oxidative damage to tissues (Huang et al . ; Liang et al . ) although its exact mechanism has not been demonstrated.…”
Section: Vitaminsmentioning
confidence: 99%
“…It participates in synthesis of steroid hormones and collagen (Lightner et al 1979;Cavalli et al 2003;Mustafa et al 2013), tolerance to toxicants and environmental stressors (Merchie et al 1995). It has also been proposed to be potentially beneficial in increasing immune response (Roosta et al 2014;Kim & Kang 2015;Shahkar et al 2015) and reducing oxidative damage to tissues (Huang et al 2017;Liang et al 2017) although its exact mechanism has not been demonstrated. Vitamin C also promotes beneficial effects on serum bactericidal activity, phagocytic activity, antibody levels and lysozyme activity (Ren et al 2005).…”
Section: Vitaminsmentioning
confidence: 99%